Importance of medical imaging in ovarian hyperstimulation syndrome post suction and evacuation of H-mole: a rare case report and literature review - Jha, Sailendra; Shah, Abhishek; Shah, Deepa; Pande, Prabhat B.; Devkota, Pragya; Rauniyar, Amit K.; Ghimire, Amit; Poudel, Sandesh; Vaidya, Sunisha; Oli, Alina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Hydatidiform mole (H-mole) is a gestational trophoblastic disorder caused by abnormal fertilization, often presenting with elevated β-HCG levels and abnormal uterine findings. A rare complication is spontaneous Ovarian Hyperstimulation Syndrome (OHSS), usually associated with fertility treatments but occasionally triggered by high endogenous β-HCG levels. We report a case of a 17-year-old primi-gravida who developed OHSS following suction and evacuation of a complete H-mole. Despite of initial management, she presented later with ovarian enlargement, lung nodules, and rising β-HCG, indicating high-risk gestational trophoblastic neoplasia (GTN) for which imaging played a key role in identifying complications. She responded well to EMA-CO chemotherapy with normalization of β-HCG. This case emphasizes the importance of post-evacuation monitoring and the critical role of imaging in diagnosing and managing rare but serious complications like spontaneous OHSS.